On the Forecast of Thai Industry Value Added - Rojniruttikul, Nuttawut; Vajrapatkul, Adirek (My University, 2021)
Industry value added is a crucial factor that keep the manufacturers to survive in the high business competitive environment. Also it encourage the economic growth by offering the opportunity to generate high income from international trade. Thus achieving in creating high level of value added become the point of interest for both manufacturers and governments. Hence, to investigate what determine such value added. This work is designed to present the effects of some business and economic variables, namely gross domestic product, consumer price index, domestic credit to the private sector, and gross capital formation on industry value added in the context of Thailand by utilizing the Bayesian vector autoregression (BVAR) model with the 58 periods of annual modified data running from 1960 to 2019. This model shows the interactions between these five variables and the forecast of industry value-added. The results from this work revealed that there exist the Granger Causality and reactions between domestic credit to private, domestic capital formulation, domestic general price level, growth of the gross domestic product, and industry value-added. Thus, we recommend that government authorities should 1) encourage more credit to manufacturers, 2) invest more in industrial-facilitate infrastructure and support more on private investment in capital formulation, 3) induce more country income, and 4) control the general price level within the country.
Keywords: Bayesian vector autoregression; Consumer price index; Domestic credit to the private sector; Gross capital formation; Gross Domestic Product; Industry value-added